Chemical compositions and α-glucosidase inhibitory effects of anthocyanidins from blueberry, blackcurrant and blue honeysuckle fruits. (30th November 2019) - Zhang, Jiangtao; Sun, Lijun; Dong, Yushan; Fang, Zhongxiang; Nisar, Tanzeela; Zhao, Ting; Wang, Zi-Chao; Guo, Yurong
Highlights: Anthocyanidins exhibited higher α-glucosidase inhibition effects than anthocyanins. Anthocyanidins were mixed-type inhibitors and inhibited through a static procedure. Anthocyanidins occupied the active site of enzyme and avoided the entrance of p NPG. Anthocyanidins from berry fruits can be used as potential α-glucosidase inhibitors. Abstract: The chemical compositions and α-glucosidase inhibitory activities of anthocyanins extracted from blueberry, blackcurrant and blue honeysuckle fruits and their acid hydrolysates (anthocyanidins) were analysed. Those anthocyanins were glycosidic anthocyanins that converted to anthocyanidins during acid hydrolysis, leading to increases in their α-glucosidase inhibitory activities (expressed as IC50 values) from 0.232, 0.152 and 0.188 to 0.113 to 0.005 and 0.025 mg/mL. The potential inhibitory mechanism of these anthocyanidins was then investigated through inhibition kinetics, fluorescence quenching and docking simulations. The results showed the following: 1) all anthocyanidins were mixed-type inhibitors of α-glucosidase and they bind more tightly to free α-glucosidase as compared to the α-glucosidase-substrate complex; 2) anthocyanidin inhibition of α-glucosidase was a static procedure, presumably driven by hydrophobic associations and hydrogen bonding; and 3) all anthocyanidins were inserted into the active site of α-glucosidase and avoided the entrance of p -nitrophenyl- a -D-glucopyranoside. This study is valuable for anthocyanidins as potential α-glucosidase inhibitors.